Clinical practice guideline for the diagnosis and treatment of hemophilia for the Peruvian Social Security (EsSalud) - Mendoza Ordoñez, Saúl (2018)
Introduction. Hemophilia is a rare congenital bleeding disorder; which requires interdisciplinary, complex, and often expensive management. The objective of this clinical practice guideline (CPG) is to provide evidence-based clinical recommendations for the evaluation and management of patients with hemophilia in the Peruvian Social Security (EsSalud). Methods. A local elaboration group (GEG-Local) was established, conformed by specialists in hematology and methodologists. The GEG-Local formulated 8 clinical questions to be answered by this CPG. We searched for and selected hemophilia CPGs that answered the questions posed and obtained a score higher than 60% in domains 1 and 3 of the Appraisal of Guidelines for Research and Evaluation II (AGREE-II). During 2016, bibliographic searches were conducted in Pubmed, EMBASE and the Cochrane library, to update 7 clinical questions of the preselected CPG, and to answer a question de novo. In regular work meetings, the GEG-Local reviewed the evidence and formulated the recommendations and flowcharts using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Finally, the CPG was approved with Resolution No. 32-IETSI-ESSALUD-2016. Results. This CPG addressed 8 clinical questions. Based on these questions, 22 recommendations were formulated (three strong recommendations and 19 weak recommendations) and four flowcharts. Conclusion. This article is the summary of the EsSalud CPG, in which the available scientific evidence on the diagnosis and treatment of hemophilia was assessed.